La Red de Bibliotecas del Instituto Cervantes: una visión actual - Moreno Cámara, Alicia; Prieto Gutiérrez, Juan José (Revista General de Información y Documentación, 2009)
The Network of Libraries of Cervantes Institute, heiresses of the antique Spanish Houses and the Cultural Centres, distributed around of the different continents, has known to agglutinate and to be the impulse stated for the diffusion of the language and the Spanish and Hispano-American culture. The libraries, in direct collaboration with the Cervantes Institute, offer a daily and continuous service to the users who go to the Institute, for consult collections, loan, reproduction, specialized bibliographical information, access to data bases... etc. Currently they are one of the bastions that better represent to us outside and within our borders.